The Effect of the Tianma Gouteng Yin Formula Therapy on Patients with Vertigo of Liver Hyperactivity Syndrome - Heriyanto, Heriyanto; Kang, Hari Iskandar; Aditya, Stefanus; Xaverius, Franciscus; Anwar, La Ode Muhamad (Jurnal Sehat Indonesia (JUSINDO), 2025)
Based on WHO data in 2019, vertigo was experienced by 7.4% of the global population aged 18–79 years. In Indonesia, Basic Health Research (2023) reported a very high prevalence of vertigo, making it the third most common complaint in hospitals, with a prevalence rate of 50% in the 40–50-year age group. A preliminary survey at the Divine Nature Health Center in 2024 confirmed the high number of vertigo cases, with an average of 500 patients every three months, of which liver yang hyperactivity syndrome was the most frequent (300 patients per three months). This research aims to determine the effect of the Tianma Gouteng Yin formula therapy on vertigo patients with liver yang hyperactivity syndrome. The study employed a quantitative method using a pre-experimental one-group pre–post test design. Fifty research subjects were selected through purposive sampling between March and June 2025. Subjects aged 40–50 years received Tianma Gouteng Yin therapy twice daily at 2 grams for one week. Measurements were conducted using the VSS-SF questionnaire before and after therapy. Results showed that the average VSS-SF score decreased from 10.6 (pretest) to 2.96 (posttest). Statistical analysis indicated an asymp. sig. value of 0.000 (p < 0.05) and an effect size (r = -0.869), demonstrating that Tianma Gouteng Yin formula therapy has a significant and strong effect in reducing VSS-SF scores in vertigo patients with liver yang hyperactivity syndrome.